Anti-Inflammatory Activity of Lactobacillus on Carrageenan-Induced Paw Edema in Male Wistar Rats. (22nd February 2012) - Amdekar, Sarika; Roy, Purabi; Singh, Vinod; Kumar, Avnish; Singh, Rambir; Sharma, Poonam
Abstract : Introduction . Lactobacillus casei and Lactobacillus acidophilus were used to assess the anti-inflammatory properties in carrageenan induced acute inflammatory model. Materials and Methods . Diclofenac sodium was used as standard drug at concentration of 150 mg/kg of body weight. Culture of Lactobacillus 2 × 10 7 CFU/ml was given orally. Edema was induced with 1% carrageenan to all the groups after one hour of the oral treatments. Paw thickness was checked at t = 1, 2, 3, 4, 5, and 24 hours. Stair climbing score and motility score were assessed at t = 24 hours. Cytokines assay for IL-6, IL-10, and TNF-α was performed on serum samples. Results . Lactobacillus showed a statistically significant decrease in paw thickness at P < 0.001 . L. acidophilus and L. casei decreased by 32% and 28% in paw thickness. They both significantly increased the stair climbing and motility score. Lactobacillus treatment significantly downregulated IL-6 and TNF-α while upregulated IL-10 at P < 0.0001 . Conclusion . L. casei and L. acidophilus significantly decreased the inflammatory reactions induced by carrageenan. This study has also proposed that Lactobacillus ameliorated the inflammatory reaction by downregulating the proinflammatory cytokines pathway.